2021
DOI: 10.21203/rs.3.rs-141832/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment and Predicting of LULC by Kappa Analysis and CA Markov model using RS and GIS Techniques in Udham Singh Nagar District, India

Abstract: In this study an attempt to generate the LULC maps and investigate change detection analysis over a period of 22 years using Landsat satellite images of 1994, 2000, and 2016 and to predict the LULCC for the year 2016-2032 using CA Markov model in Udham Singh Nagar district, Uttarkhand. Satellite images of Landsat 5 TM, Landsat 7 ETM+, and Landsat 8 OLI sensor of nominal spatial resolution 30m were used. Supervised image classifications with the help of parallel pipe algorithm were used in this study. The valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Accuracy makes the value of information of the resulted data to the user. This procedure employs three geospatial tools in ArcMap: Construct Accuracy Assessment Points, Modify Accuracy Assessment Points, and Calculate Confusion Matrix (Arumugam et al, 2021).…”
Section: -The Accuracy Assessment Estimator and The Kappa Coefficient...mentioning
confidence: 99%
“…Accuracy makes the value of information of the resulted data to the user. This procedure employs three geospatial tools in ArcMap: Construct Accuracy Assessment Points, Modify Accuracy Assessment Points, and Calculate Confusion Matrix (Arumugam et al, 2021).…”
Section: -The Accuracy Assessment Estimator and The Kappa Coefficient...mentioning
confidence: 99%
“…Contrarily, the overall accuracy quantifies the percentage of correctly identified pixels throughout the complete image (Arumugam et al 2021). The following equation ( 2) is used to compute it:…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…As the present year data on area covered by crops and area of built-up land is not available, previous year (2019-20) data were taken from the Directorate of Economics and Statistics official website (https://eands.dacnet.nic.in) whereas actual forest area was retrieved from the Forest Survey of India, 2019 report. Arumugam et al [21] reported that the waterbodies area in Udham Singh Nagar is 6,272 ha. As the data regarding the 'Other' class was not available, this class is not taken in comparison.…”
Section: Data Sources and Collectionmentioning
confidence: 99%